Spain and the Holocaust: between salvation and condemnation to extermination for Jewish population - Simó Sánchez, Marta (Hispania Nova, 2019)
The role played by Spain during the Holocaust remains a matter of debate. It has been often defended its neutrality with respect to Nazi Germany and its intention to help and save Jewish population. In this article, it will be analysed through testimonies and documents, which were the policies to the Jews both, the ones who had arrived in Spain in the period prior to 1933 and those who sought shelter during the years of Nazism (1933-1945). The randomness in the treatment received as well as their fate is a characteristic of these policies. Rejection to help or immobility in deciding what to do with them condemned many of them to death.
Keywords: Holocaust; Jews; Spain; Gestapo; Emigration